Amber Brown is green with envy - Danziger, Paula, 1944-2004 (Danziger, Paula, 1944-2004. A is for Amber., 2003)
Fourth-grader Amber Brown must make some important decisions when her mother and Max move their wedding date up and prepare to buy a house together, while her father makes some bad choices of his own.